Onion Diseases in the Libyan Jamahiriya - ABUGHNIA, ABDULNABI; ADAM, FAWZI (The Libyan Journal of Agriculture, 2023)
Field diagnosis showed that downy mildew caused by Peronospora destructor (Berk.) Casp. and Purple blotch caused by Alternaria pori (Ell.) Cif. were the two major diseases which causes economic losses to onion. Fusarium oxysporum f.sp. cepae Schlect. emend. Snyd. & Hans, and Fusarium roseum Link, emend. Snyd. & Hans, and other Fusarium spp., were consistently isolated from onion bulbs and may be responsible for some of the losses occured in the field and in storage. Post harvest studies indicate that bacterial soft rot disease caused by Erwinia spp. and Pseudomones spp. were primirily responsible for over 50% losses of the crop. Other microorganisms were isolated from onion such as Aspergillus spp., Penicillium spp. Rhizoctonia spp., and Pyreochaeta spp.